Perception of risk from environmental hazards : a comparative study of underrgraduates in the United States and Costa Rica - Westmoreland, Gail (Atlanta, Ga., 1994)
Tesis (doctorado en filosofía)--Emory University, 1994.
Keywords: SALUD -- ASPECTOS AMBIENTALES